Nanotechnology A Path To Nanovaccine - DR TARALA D NANDEDKAR, (International Journal of Pharma and Bio Sciences, 2012)
Nanotechnology has gained importance in medicine and is referred to as nanomedicine.Various tools of nanomaterials have been investigated for their application in imaging, diagnosis and therapy; these are carbon nanotubes, fullerenes, cantilevers, liposomes, quantum dots, nanoshells, nanoparticles, dendrimers etc. Antigens/epitopes can be tagged to nanomaterials for immunization/vaccination. Different routes of administration have been tried for nanovaccines which include oral, nasal, intradermal and microneedle patches. Due to their small size and large surface area these nanoparticles are useful as nanovaccines. To enhance the immunogenicity of small peptides/epitopes in nanovaccines polymers, immune stimulating complexes (ISCOMs), virus-like particles (VLPs), nanobeads and nanocarriers have been used as adjuvants. These adjuvants are safeand enhance the immune response. Although nanoparticles have numerous advantages, they have certain drawbacks as well. Therefore, study of toxicity of nanoparticles is essential. In vitro systems and in vivo models have been developed to answer the safety of the nanoparticles/nanodevices.